2022
DOI: 10.3389/fendo.2022.1025005
|View full text |Cite
|
Sign up to set email alerts
|

Association between uric acid and height during growth hormone therapy in children with idiopathic short stature

Abstract: BackgroundSerum uric acid (UA) within appropriate levels is reported to be beneficial in patients with idiopathic short stature (ISS). This study aimed to evaluate the association between serum UA levels and height standard deviation scores (SDS) in patients with ISS during growth hormone (GH) therapy.MethodsA longitudinal study (LG Growth Study) of 182 children (mean age: 7.29±2.60 years) with ISS was performed. All participants were in the prepubertal stage and treated with GH, and the data within a treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A study revealed a non-linear relationship between UA concentrations and IGF-1 SDS in children and adolescents with ISS, where IGF-1 SDS was positively correlated with appropriate serum UA concentrations, while too high or too low serum UA levels were associated with lower IGF-1 SDS values ( 11 ). Another longitudinal study of 182 prepubertal ISS children treated with rhGH for 30 months showed that UA was significantly associated with height SDS after controlling for sex, age, and BMI SDS, and no statistical correlation was observed despite similar trends in increasing IGF-1 SDS and UA levels ( 34 ). In boys with obesity and NAFLD, no change was observed in UA levels at months 3 and 6 of rhGH administration ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study revealed a non-linear relationship between UA concentrations and IGF-1 SDS in children and adolescents with ISS, where IGF-1 SDS was positively correlated with appropriate serum UA concentrations, while too high or too low serum UA levels were associated with lower IGF-1 SDS values ( 11 ). Another longitudinal study of 182 prepubertal ISS children treated with rhGH for 30 months showed that UA was significantly associated with height SDS after controlling for sex, age, and BMI SDS, and no statistical correlation was observed despite similar trends in increasing IGF-1 SDS and UA levels ( 34 ). In boys with obesity and NAFLD, no change was observed in UA levels at months 3 and 6 of rhGH administration ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…These criteria, as well as a consideration of the interpretability of group size and meaningfulness of differences in trajectories, were used to select the final trajectory model. In addition, we examined the average posterior probability and the odds of correct classification (based on the weighted posterior probability) to assess model performance [using thresholds of >.70 and ≥5.0, respectively (47, 48)].…”
Section: Developmental Changes In Salivary Uric Acid Concentrationsmentioning
confidence: 99%
“…Furthermore, recent evidence suggests that height and IR are also negatively correlated 16 , suggesting that individuals with short stature have a significantly increased risk of developing CVD and IR. Additionally, a longitudinal study conducted in children with idiopathic short stature revealed a correlation between SUA levels and height standard deviation score (SDS) 17 . Furthermore, short stature in childhood is associated with health status in adulthood 18 .…”
Section: Introductionmentioning
confidence: 99%